Electrochemical sensor for uric acid detection and preparation method thereof

By using a combination of glassy carbon electrodes, polymer layers and porous aromatic skeleton layers in the uric acid detection electrochemical sensor, the problems of poor selectivity, low stability and high detection limit of existing uric acid detection methods are solved, and a detection effect with high selectivity, high sensitivity and low detection limit is achieved, which is suitable for clinical diagnosis.

CN120668751AActive Publication Date: 2025-09-19CHONGQING UNIV OF POSTS & TELECOMM
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510920258.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-04
Publication Date
2025-09-19
Estimated Expiration
2045-07-04

AI Technical Summary

Technical Problem

Existing uric acid detection methods have problems such as poor selectivity, low stability, high detection limit and weak anti-interference ability. In particular, the application of electrochemical sensing technology in clinical diagnosis has not yet reached an ideal state.

Method used

An electrochemical sensor is formed by using a glassy carbon electrode as the basis, a polymer layer made by a cross-linking agent and a porous aromatic skeleton layer. Specifically, the polymer layer is composed of glutaraldehyde, perfluorosulfonic acid polymer, polyaniline and polyvinylidene fluoride, and the porous aromatic skeleton layer is made of porous PAF-5 material.

Benefits of technology

The selectivity, sensitivity and stability of the sensor are improved, the detection limit is reduced, and it has good prospects for clinical diagnostic applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120668751A_ABST
    Figure CN120668751A_ABST
Patent Text Reader

Abstract

The invention discloses an electrochemical sensor for uric acid detection and a preparation method thereof, and the electrochemical sensor comprises an electrode sensing layer adopting a glassy carbon electrode; the polymer layer is prepared from a cross-linking agent and comprises at least one of glutaraldehyde, a perfluorosulfonic acid polymer, polyaniline and polyvinylidene fluoride; and the porous aromatic skeleton layer is made of a porous PAF-5 material. The electrochemical sensor for uric acid detection is only composed of the electrode sensing layer, the polymer layer and the porous aromatic skeleton layer, and is simple and clear in structure and easy to prepare. In the sensor, the polyvinylidene fluoride is added into the polymer layer and the porous PAF-5 material is added into the porous aromatic skeleton layer, so that the amplification of a uric acid detection signal is realized, the selectivity, the sensitivity and the stability of a sensing platform are improved, the detection limit is reduced, and the sensor has a good clinical diagnosis application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical sensing, and in particular to an electrochemical sensor for uric acid detection and a preparation method thereof. Background Art

[0002] Uric acid is a product of purine metabolism in the human body. When the human body is in a healthy state, uric acid levels fluctuate within a normal range. Uric acid is a biomarker for many diseases. In clinical diagnosis, abnormal uric acid levels in blood, urine, or cerebrospinal fluid indicate the onset of disease. Uric acid crystals in the joints can cause gout, while crystals in the kidneys can cause kidney stones. High uric acid levels lead to hyperuricemia, which, in turn, is related to insulin and indirectly leads to diabetes. In addition to the above-mentioned diseases directly caused by abnormal uric acid levels, diseases such as neurological diseases, certain cancers, obesity, and pregnancy-induced hypertension are also closely related to abnormal uric acid levels.

[0003] Currently, the commonly used methods for uric acid detection include colorimetry, mass spectrometry, fluorescence, and electrochemical sensing technology. Among them, colorimetry has many similar colors, which can easily make it difficult to distinguish in clinical diagnosis, and the instability of the color reaction leads to reduced measurement accuracy. Mass spectrometry and fluorescence methods are expensive instruments, have high maintenance costs, require professional testing personnel, have complex sample preparation, and take long analysis times, making them unsuitable for widespread application in clinical testing. Electrochemical sensing technology has the advantages of high cost-effectiveness, short detection time, no need for complex test material preparation, low experimental environment requirements, and great portability. Therefore, the application of electrochemical sensing technology in clinical diagnosis is very suitable. However, there are still some problems with the current electrochemical sensing technology for uric acid. It is necessary to modify the materials to capture more uric acid molecules, improve the stability and selectivity of the sensing platform, and reduce the detection limit.

[0004] Therefore, there is an urgent need to develop uric acid electrochemical sensors with the advantages of high selectivity, high stability, low detection limit, strong anti-interference ability and repeatability. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide an electrochemical sensor for uric acid detection and a preparation method thereof.

[0006] To achieve the above object, the technical solution of the present invention is:

[0007] In a first aspect, the present invention provides an electrochemical sensor for uric acid detection, comprising:

[0008] The electrode sensing layer uses glassy carbon electrodes;

[0009] a polymer layer made of a cross-linking agent including at least one of glutaraldehyde, perfluorosulfonic acid-based polymer, polyaniline, and polyvinylidene fluoride;

[0010] The porous aromatic skeleton layer is made of porous PAF-5 material.

[0011] As a preferred embodiment of the present invention, the thickness of the electrode sensing layer is 1000 nanometers, and the diameter of the electrode core of the electrode sensing layer is 2000-4000 micrometers.

[0012] As a preferred embodiment of the present invention, the thickness of the polymer layer is 400-600 nanometers.

[0013] As a preferred embodiment of the present invention, the thickness of the porous aromatic skeleton layer is 1000-3000 nanometers.

[0014] As a preferred embodiment of the present invention, the polymer layer is made of polyvinylidene fluoride, and the weight average molecular weight of the polyvinylidene fluoride is about 400,000 Da.

[0015] As a preferred embodiment of the present invention, the porous PAF-5 material is formed by polymerization of 1,3,5-tris(4-bromophenyl)benzene monomer, the average particle size of the porous PAF-5 material is 200 nanometers, and the mass fraction of the porous PAF-5 material in the porous aromatic skeleton layer is greater than 95%.

[0016] In a second aspect, the present invention further provides a method for preparing the electrochemical sensor for uric acid detection as described above, comprising the following steps:

[0017] S1: forming a polymer layer on one side of the electrode sensing layer;

[0018] S2: forming a porous aromatic skeleton layer on a side of the polymer layer away from the electrode sensing layer.

[0019] As a preferred embodiment of the present invention, step S1 includes:

[0020] S101: The electrode sensing layer is polished using Al2O3 powder, and ultrasonically cleaned in ethanol and deionized water, respectively, and finally activated in dilute sulfuric acid;

[0021] S102: loading a cross-linking agent onto the treated surface of the electrode sensing layer at room temperature, and drying the layer under infrared light to form a polymer layer.

[0022] As a preferred embodiment of the present invention, step S2 includes: loading a porous PAF-5 material on a side of the polymer layer away from the electrode sensing layer at room temperature, and drying under infrared light to form a porous aromatic skeleton layer.

[0023] As a preferred embodiment of the present invention, the porous PAF-5 material used to form the porous aromatic skeleton is prepared by the following steps:

[0024] Step 1: Under a nitrogen environment, dissolve bis(1,5-cyclooctadiene)nickel(0), 2,2'-bipyridine and 1,5-cyclooctadiene in anhydrous N,N-dimethylformamide, and react at 60-80° C. for 1-3 hours to obtain a first mixed solution;

[0025] Step 2: Add 1,3,5-tris(4-bromophenyl)benzene to the first mixed solution, react at 60-80° C. for 24 hours, wash and vacuum dry to obtain the product.

[0026] After adopting the above technical solution, compared with the prior art, the electrochemical sensor for uric acid detection and the preparation method thereof provided by the present invention have the following beneficial effects:

[0027] The electrochemical sensor for uric acid detection provided by the present invention consists solely of an electrode sensing layer, a polymer layer, and a porous aromatic framework layer. It boasts a simple, clear structure and is easy to prepare. By incorporating polyvinylidene fluoride into the polymer layer and porous PAF-5 into the porous aromatic framework layer, the sensor amplifies the uric acid detection signal, improving the selectivity, sensitivity, and stability of the sensing platform and lowering the detection limit. This sensor has promising clinical diagnostic applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The accompanying drawings are part of the present invention and are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention, but do not constitute an undue limitation of the present invention. Obviously, the drawings described below are only some embodiments. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without inventive effort. In the accompanying drawings:

[0029] Figure 1 shows a schematic diagram of an electrochemical sensor provided by an embodiment of the present invention;

[0030] Figure 2 shows an electrochemical characterization diagram provided by an embodiment of the present invention;

[0031] Figure 3 Shows an SEM image of a porous aromatic skeleton layer provided by an embodiment of the present invention;

[0032] Figure 4 shows a cyclic voltammetry scan rate diagram provided by an embodiment of the present invention;

[0033] Figure 5A linear relationship diagram of the electrochemical sensor provided by an embodiment of the present invention for different uric acid concentrations is shown;

[0034] Figure 6 A linear relationship diagram of the glassy carbon sheet provided by an embodiment of the present invention and different uric acid concentrations is shown.

[0035] It should be noted that these drawings and textual descriptions are not intended to limit the conceptual scope of the present invention in any way, but rather to illustrate the concept of the present invention for those skilled in the art by referring to specific embodiments. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. The following embodiments are used to illustrate the present invention but are not used to limit the scope of the present invention.

[0037] like Figure 1 As shown, the present application provides an electrochemical sensor for uric acid detection, comprising an electrode sensing layer, a polymer layer, and a porous aromatic skeleton layer stacked in sequence. The sensor has a simple and clear structure and is easy to prepare.

[0038] Specifically, the electrode sensing layer utilizes a glassy carbon electrode with a thickness of 1000 nanometers and an electrode core diameter of 2000-4000 microns. Preferably, the electrode core diameter of the electrode sensing layer is 3000 microns. An electrode core diameter that is too small results in a low electrochemically active area of ​​the sensor; an electrode core diameter that is too large results in excessively high costs, reducing cost effectiveness.

[0039] Furthermore, the polymer layer is made of a cross-linking agent. The cross-linking agent has high electrochemical stability and does not affect the performance of the entire electrochemical sensor. The structure of the polymer layer is stable. The thickness of the polymer layer is 400-600 nanometers, preferably 500 nanometers. If the thickness of the polymer layer is too high, the permeability of the material will be reduced, which will hinder the binding of uric acid to the sensor. If the thickness of the polymer layer is too low, it will affect the binding of the porous aromatic skeleton layer to the sensor surface and may even cause it to fall off.

[0040] The cross-linking agent for preparing polymer layer adopts at least one of glutaraldehyde, perfluorosulfonic acid polymer, polyaniline and polyvinylidene fluoride, especially preferably polyvinylidene fluoride.After polyvinylidene fluoride contacts with porous aromatic skeleton layer material, it can be firmly fixed on sensor surface, so that overall material stability is improved together again, and polyvinylidene fluoride has good antioxidant ability simultaneously, makes sensing platform voltage more stable, reduces the error of data. In a preferred embodiment, the weight average molecular weight of the cross-linking agent polyvinylidene fluoride for preparing polymer layer is about 400000Da (it is suggested to increase a certain range, such as 380000-420000Da, and select the reason of the weight average molecular weight or the beneficial effect brought).

[0041] Furthermore, the porous aromatic skeleton layer is made of porous PAF-5 material and has a thickness of 1000-3000 nanometers, preferably 2000 nanometers. If the porous aromatic skeleton layer is too thin, it will affect the signal amplification factor; if the porous aromatic skeleton layer is too thick, it will hinder the contact between uric acid and the sensor surface.

[0042] Preferably, the porous PAF-5 material is polymerized from 1,3,5-tris(4-bromophenyl)benzene monomers, the average particle size of the porous PAF-5 material is 200 nanometers, and the mass fraction of the porous PAF-5 material in the porous aromatic skeleton layer is greater than 95%.

[0043] Porous aromatic skeletons are a new type of porous organic material. Traditional diamond materials are usually connected by C-C covalent bonds. Although this produces a significantly stable structure, the overly tight connection leads to a reduction in porosity. The porous aromatic skeleton uses aromatic building blocks as monomers and, through different polymerization reactions, generates different porous materials while still maintaining an excellent stable structure. Since there are more opportunities to expose the aromatic structure, the effective specific surface area is greatly increased. The porous PAF-5 material is a porous organic polymer that contains only benzene rings after polymerization. Due to its many pores, large specific surface area, and high stability, it greatly increases the sensitivity of the sensor for uric acid detection, reduces the detection limit, and improves the repeatability of the experiment.

[0044] In this electrochemical sensor, by adding polyvinylidene fluoride to the polymer layer and porous PAF-5 material to the porous aromatic skeleton layer, the uric acid detection signal is amplified, the selectivity, sensitivity and stability of the sensing platform are improved, and the detection limit is reduced.

[0045] This specification also provides a method for preparing a porous PAF-5 material for preparing a porous aromatic skeleton layer, which specifically includes the following steps:

[0046] Step 1: Under a nitrogen environment, dissolve bis(1,5-cyclooctadiene)nickel(0), 2,2'-bipyridine and 1,5-cyclooctadiene in anhydrous N,N-dimethylformamide, and react at 60-80° C. (preferably 70° C.) for 1-3 h (preferably 2 h) to obtain a first mixed solution;

[0047] Step 2: Add 1,3,5-tris(4-bromophenyl)benzene to the first mixed solution, react at 60-80° C. (preferably 70° C.) for 24 hours, wash and vacuum dry to obtain the product.

[0048] Preferably, the porous PAF-5 material used in the subsequent examples of this application is obtained by the following steps:

[0049] In a nitrogen atmosphere, 1 g of bis(1,5-cyclooctadiene)nickel (0), 0.3 g of 2,2'-bipyridine, and 100 μL of 1,5-cyclooctadiene were added to 40 mL of anhydrous N,N-dimethylformamide. The mixture was then stirred at 70°C for 2 h. After the reaction was complete, 0.5 g of 1,3,5-tris(4-bromophenyl)benzene was added and stirred at 70°C for 24 h to obtain a crude product. The PAF-5 product was isolated by acidification and repeatedly washed with deionized water, tetrahydrofuran, and chloroform. The product was then dried in a vacuum drying oven to obtain pure PAF-5.

[0050] The present invention also provides a method for preparing the electrochemical sensor for uric acid detection as described above, comprising at least the following steps:

[0051] S1: providing an electrode sensing layer and forming a polymer layer on one side of the electrode sensing layer;

[0052] S2: forming a porous aromatic skeleton layer on the side of the polymer layer away from the electrode sensing layer;

[0053] Specifically, in the process of preparing the above sensor, step S1 further includes:

[0054] S101: Polish the electrode sensing layer using Al2O3 powder, ultrasonically clean it in ethanol and deionized water, and finally activate it in dilute sulfuric acid. This physical polishing removes impurities or oxide layers on the electrode surface, reducing experimental errors.

[0055] S102: at room temperature, loading a cross-linking agent (preferably polyvinylidene fluoride) on the surface of the electrode sensing layer, and drying under infrared light irradiation to form a polymer layer.

[0056] Furthermore, step S2 further includes: loading the porous PAF-5 material on a side of the polymer layer away from the electrode sensing layer at room temperature, and drying under infrared light irradiation to form a porous aromatic skeleton layer.

[0057] The electrochemical sensor for uric acid detection in this application is further described below with reference to the following examples:

[0058] Example 1:

[0059] Provide a glassy carbon electrode and perform mechanical polishing on the electrode. Add an appropriate amount of large-diameter Al2O3 powder to the electric polishing machine, and then add deionized water to make it into a slurry state. After polishing for 1 minute, ultrasonically clean it in ethanol and deionized water respectively. Repeat the above steps again, except that the large-diameter Al2O3 powder is replaced with small-diameter Al2O3 powder. After ultrasonic cleaning, blow dry the electrode surface with nitrogen, activate it in 0.5M dilute sulfuric acid, and use cyclic voltammetry. Electrochemical workstation parameter settings: initial potential: -1V; final potential: 1V; scan speed: 50mV / s; sampling interval: 5mV; number of scan segments: 50 segments; initial scan direction: forward. Through the above operations, impurities or oxide layers on the surface of the glassy carbon electrode are removed, and experimental errors are reduced.

[0060] After treating the glassy carbon electrode, a polyvinylidene fluoride solution was loaded onto the surface of the glassy carbon electrode and dried under infrared light to form a polymer layer. A porous PAF-5 material was then loaded onto the side of the polymer layer away from the electrode sensing layer and dried under infrared light to form a porous aromatic skeleton layer.

[0061] Example 2:

[0062] The only difference between the embodiment and embodiment 1 is that the glassy carbon electrode is replaced with a glassy carbon sheet.

[0063] Comparative Example:

[0064] The difference between this comparative example and the embodiment is only whether polyvinylidene fluoride and PAF-5 are added.

[0065] The electrochemical sensors obtained in Example 1, Example 2, and the comparative example were used to perform uric acid electrochemical response tests in phosphate buffer.

[0066] pass Figure 2 From the electrochemical characterization curves of Example 1 and the comparative example, it can be concluded that when the electrode surface is modified with the cross-linking agent polyvinylidene fluoride and the porous PAF-5 material, the current response signal to the same concentration of uric acid is amplified by about 4.5 times, indicating that the addition of the polymer layer and the porous aromatic skeleton layer greatly improves the performance of the sensor for uric acid detection.

[0067] refer to Figure 3 It can be seen that the PAF-5 material used in Example 1 and Example 2 has a large number of porous structures under a scanning electron microscope. The structure is compact and stable, and the specific surface area is increased due to the porous structure.

[0068] refer to Figure 4 The electrode from Example 1 was immersed in 5 mL of phosphate buffer. Cyclic voltammetry was used. Electrochemical workstation parameters were set as follows: initial potential: -1 V; final potential: 1 V; sampling interval: 5 mV; number of scan segments: 50; initial scan direction: forward. Scan rates were: 30, 50, 70, 90, 110, 130, 150, 170, 190, and 210 mV / s. Figure 4 The results showed that the 1 / 2 power of the scan rate was proportional to the current response value, indicating that the uric acid sensing process on the sensor is a diffusion-controlled process, so increasing the active sites on the sensor can amplify the current signal.

[0069] Phosphate buffer was used to prepare different concentrations of uric acid: 1, 2, 5, 10, 50, 100, 500, and 1000 μM. The electrochemical method employed the current-time method, with the following electrochemical workstation parameters set: run time: 4000 s; operating voltage: 0.2 V; sampling interval: 0.1 mV; and pause time: 2 s. First, 20 mL of phosphate buffer was added to the electrolytic cell. After the current stabilized, different concentrations of uric acid were added dropwise each time the current corresponding to a uric acid concentration stabilized, varying the uric acid concentration in the cell.

[0070] refer to Figure 5 It can be seen that the linear regression equation obtained by electrochemically testing uric acid using Example 1 is: I = 7.17E-8 + 6.09E-9 [uric acid concentration] (μM) (R 2 =0.99716), the detection limit is 15.5 nM (SNR=3), and the linear range is: 0.186-46.055 μM. This shows that the sensor has an excellent linear relationship in the range of 0.186-46.055 μM and a low detection limit.

[0071] refer to Figure 6 It can be seen that the linear regression equation obtained by electrochemically testing uric acid using Example 2 is: I = 2.59E-6 + 8.20-8 [uric acid concentration] (μM) (R 2 =0.99478), the detection limit was 0.59 μM (SNR = 3), and the linear range was 1.766-46.055 μM. This indicates that the sensor has excellent linearity in the range of 1.766-46.055 μM, but the detection limit is not as good as that of Example 1. The success of Example 2 demonstrates the potential of this invention for the subsequent preparation of portable sensing platforms.

[0072] The above description is merely a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as above in terms of a preferred embodiment, it is not intended to limit the present invention. Any technician familiar with this patent can make slight changes or modifications to equivalent embodiments of equivalent changes using the above-mentioned technical contents without departing from the scope of the technical solution of the present invention. The implementation schemes in the above-mentioned embodiments can also be further combined or replaced. However, any simple modifications, equivalent changes and modifications made to the above-mentioned embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the solution of the present invention.

[0073] In the description of this specification, the reference terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art can combine and combine different embodiments or examples described in this specification and features of different embodiments or examples without contradiction.

[0074] In the description of the present invention, it should be noted that the terms "upper", "lower", "front", "back", "left", "right", "vertical", "inside", "outside", etc., indicating directions or positional relationships, are based on the directions or positional relationships shown in the accompanying drawings. They are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific direction, be constructed and operated in a specific direction. Therefore, they cannot be understood as limiting the present invention.

[0075] In the description of the present invention, it should be noted that, unless otherwise expressly specified or limited, the terms "mounted," "connected," and "connected" should be understood broadly. For example, they may refer to fixed, detachable, or integral connections; mechanical or electrical connections; and direct or indirect connections through an intermediary. Those skilled in the art will understand the specific meanings of the above terms in the present invention based on the specific circumstances.

[0076] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of the technical features being referred to. Thus, a feature identified as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, "plurality" means two or more, unless otherwise specifically defined.

Claims

1. An electrochemical sensor for uric acid detection, characterized in that: Including the following stacked settings: The electrode sensing layer uses glassy carbon electrodes; a polymer layer made of a cross-linking agent including at least one of glutaraldehyde, perfluorosulfonic acid-based polymer, polyaniline, and polyvinylidene fluoride; The porous aromatic skeleton layer is made of porous PAF-5 material.

2. The electrochemical sensor for uric acid detection according to claim 1, wherein: The thickness of the electrode sensing layer is 1000 nanometers, and the diameter of the electrode core of the electrode sensing layer is 2000-4000 micrometers.

3. The electrochemical sensor for uric acid detection according to claim 1, wherein: The thickness of the polymer layer is 400-600 nanometers.

4. The electrochemical sensor for uric acid detection according to claim 1, wherein: The thickness of the porous aromatic skeleton layer is 1000-3000 nanometers.

5. The electrochemical sensor for uric acid detection according to claim 1, wherein: The polymer layer is made of polyvinylidene fluoride, and the weight average molecular weight of the polyvinylidene fluoride is about 400,000 Da.

6. The electrochemical sensor for uric acid detection according to claim 1, wherein The porous PAF-5 material is formed by polymerizing 1,3,5-tris(4-bromophenyl)benzene monomers, the average particle size of the porous PAF-5 material is 200 nanometers, and the mass fraction of the porous PAF-5 material in the porous aromatic skeleton layer is greater than 95%.

7. A method for preparing an electrochemical sensor for uric acid detection according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1: forming a polymer layer on one side of the electrode sensing layer; S2: forming a porous aromatic skeleton layer on a side of the polymer layer away from the electrode sensing layer.

8. The preparation method according to claim 7, wherein The step S1 comprises: S101: The electrode sensing layer is polished using Al2O3 powder, and ultrasonically cleaned in ethanol and deionized water, respectively, and finally activated in dilute sulfuric acid; S102: loading a cross-linking agent onto the treated surface of the electrode sensing layer at room temperature, and drying the layer under infrared light to form a polymer layer.

9. The preparation method according to claim 7, wherein The step S2 comprises: loading a porous PAF-5 material on a side of the polymer layer away from the electrode sensing layer at room temperature, and drying the material under infrared light to form a porous aromatic skeleton layer.

10. The preparation method according to claim 7, wherein The porous PAF-5 material used to form the porous aromatic framework is prepared by the following steps: Step 1: Under a nitrogen environment, dissolve bis(1,5-cyclooctadiene)nickel(0), 2,2'-bipyridine and 1,5-cyclooctadiene in anhydrous N,N-dimethylformamide, and react at 60-80° C. for 1-3 hours to obtain a first mixed solution; Step 2: Add 1,3,5-tris(4-bromophenyl)benzene to the first mixed solution, react at 60-80° C. for 24 hours, wash and vacuum dry to obtain the product.

Citation Information

Patent Citations

  • Composite membrane modified biosensor and preparation method and application thereof

    CN101982764A

  • Method for detecting phenol compound in solution by tyrosinase biosensor

    CN104391021A

  • Wireless monitoring system and monitoring method for urea

    CN106404869A

  • Uric acid electrochemical sensor

    CN108303454A

  • Preparation method and application of nitrogen-oxygen functionalized porous aromatic framework material

    CN116751363A